Little women - Alcott, Louisa May; Quadrum Solutions (Modern Publishing, a division of Unisystems, Inc. New York, N.Y., 2010)
A simplified, abridged version of the joys and sorrows of the four March sisters as they grow into young ladies in nineteenth-century New England